2018
DOI: 10.3390/rs10081302
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the SMAP-Derived Soil Water Deficit Index (SWDI-SMAP) as an Agricultural Drought Index in China

Abstract: Abstract:China is frequently subjected to local and regional drought disasters, and thus, drought monitoring is vital. Drought assessments based on available surface soil moisture (SM) can account for soil water deficit directly. Microwave remote sensing techniques enable the estimation of global SM with a high temporal resolution. At present, the evaluation of Soil Moisture Active Passive (SMAP) SM products is inadequate, and L-band microwave data have not been applied to agricultural drought monitoring throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…The four stations are at a high elevation with a moderately steep slope. Due to the lack of SM monitoring stations at 5 cm in China, SM values at 10 cm were used instead, as in past research [41,63,64]. Although the measurement depths are inconsistent, there is a strong correlation between the SM values of the two continuous soil layers [13].…”
Section: Study Area and In Situ Soil Moisture (Sm) Measurementsmentioning
confidence: 99%
“…The four stations are at a high elevation with a moderately steep slope. Due to the lack of SM monitoring stations at 5 cm in China, SM values at 10 cm were used instead, as in past research [41,63,64]. Although the measurement depths are inconsistent, there is a strong correlation between the SM values of the two continuous soil layers [13].…”
Section: Study Area and In Situ Soil Moisture (Sm) Measurementsmentioning
confidence: 99%
“…These results suggest that topographic factors play an important role in the performance of SWDI for agricultural drought, and the results are consistent with Paredes-Trejo and Barbosa [9], who showed that agricultural drought indices obtained from satellite soil moisture tends to show poor performance in mountain regions. A possible reason is that the surface water in mountainous regions is limited due to the high potential for infiltration because of complex topography [34,58,59]. In terms of BIAS values (Figure 2b), about 85 percent of grids were between −20 % and 20%, 51 percent were between −10 % and 10%, and only 3.5 percent were over 30%.…”
Section: Evaluation Of Smap Soil Moisturementioning
confidence: 99%
“…Validation and calibration of space-borne observations by comparison with ground measurements are crucial in evaluating the quality of satellite products 17 . Therefore, in situ soil moisture monitoring systems have been established to calibrate and validate (Cal/Val) soil moisture data or brightness temperature (TB) 17 , 33 , 34 . An important factor leading to minimization of errors of satellite SM retrievals is precise matching the in situ measurement and the satellite sensing depth 11 .…”
Section: Introductionmentioning
confidence: 99%